The extremely inconvenient adventures of Bronte Mettlestone - Moriarty, Jaclyn (Scholastic Inc., 2019)
With her parents away on wonderful adventures, Bronte is happy living with her Aunt Isabella and her butler. After her parents are killed by pirates, she finds that they have left her a set of explicit instructions: she must deliver certain gifts to her father's ten sisters at very specific times. And since it is a faery will, she must follow it exactly or her hometown will be destroyed. So Bronte sets off on an exciting journey through the Empires and Kingdoms.